Pemberdayaan Masyarakat Berbasis Pondok Pesantren dalam Mewujudkan Santripreneur - Moh. Syaiful Bahri; Derry Ahmad Rizal (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
The situation in islamic boarding school education in recent years has experienced many changes, one of which is the application of entrepreneurial skills to students. This aims to provide provisions in addition to religious knowledge, but when returning to the neighborhood can live independently. This study discusses a boarding school that realizes students to become an entrepreneur, which is located at Harapan Ar-Risalah Islamic Boarding School, Bantul, Yogyakarta Special Region. Using qualitative research methods, which describe and draw data contained in the research location. There are several empowerment programs for students in realizing santripreneurs. For example the canteen program in the boarding school environment, the students are also included in managing the canteen. In addition to fostering an entrepreneurial spirit, santri are also taught to manage well. We other programs are fish farming, cooperatives, waste sorting and preparing skills in terms of education, namely as teachers. These programs are used as the initial program for entrepreneurship.